(3GdQhV GdHGSe aj MhGOK GdYeQ hGdJQGLes - (3YHO GdHGSW Hf Ndjd Hf TGgjf GdedWj, Ke GdbGgQj, Rjf GdOjf,J (B920 (3g` s
(3ChdgG (B:s
(3hHYO aEfi CQOJ Cf CLeY LejY eG hbY ef Chd GdNdaGA Edi GHJOGA GdYKeGfi jhe GdSHJ hbY ajgG (B: (3ai jhe GdSHJ eSJgd UaQ s
(3BNQgG (B:s
(3ef SfI (B868 (3JQLeI Ydi Hf eMeO Hf adGM GdeTYTY GdSjO GdTQja GdMSfi ahUd Edjg ai eOI bUjQI LOkG jcGO GdYbd dGjSYgG s
(3HChdgG agQS HNW MOjK HebOGQ SJ hQbGJs
(3ai GdeYgO JLQjOg ddeDda faSg HYfhGf GdeLeY Gdeaff HGdeYLe GdeYfhf eQJH Ydi MQha GdeYLe HQbe (B779 (3JGQjN ef MhGOK (B865 - (3SfI (B868 (3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B270 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B68s
Keywords: (3GdJGQjNs